The immature stages of Pulvinaria tenuivalvata (Newstead) (Hemiptera: Coccidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The soft scale Pulvinaria tenuivalvata (Newstead) was discovered in Egypt in 1992 and, within a few years, has become the major pest of sugarcane, especially in Upper Egypt. This paper describes the 1st-instar nymph and 2nd- and 3rd-instar female nymphs of this species and provides a key for their separation.
Keywords: Pulvinaria tenuivalvata; Saccharolecanium krugeri; Coccoidea